"It Stops Your Brain From Making Assumptions About What a Body Should Look Like": The Impact of Life Drawing on Adolescents, With Recommendations for Practitioners. (January 2019) - Swami, Viren; Shaw, Liz
Studies have shown that life drawing can have positive effects on body image in adults. Here, we examined the effect of life drawing in a sample of British adolescents ( N = 14). Participants completed measures of positive body image, appearance investment, and self-esteem before attending three life drawing sessions over 7 weeks. Following the final session, they completed the same quantitative measures and answered open-ended questions about their experiences. Analyses of quantitative data showed that participants had significantly higher positive body image and lower dysfunctional appearance investment following the final session. However, responses to the open-ended questions suggested that most participants did not believe the sessions had impacted their body image. The latter data also suggested that participants felt discomfort with adult nudity, although most also indicated that the sessions had changed their perceptions of others. Based on our results, we make a number of recommendations for practitioners.